Trends and Structures of Direct Taxation and its Share in Gross Domestic Product of Nepal - Dangal, Dil Nath; Gajurel, Ram Prasad (Economic Review of Nepal, 2019)
This study tried to analyze trends and structures of direct tax in Nepal with the adoption of descriptive method. This study, based on secondary data published by the Government of Nepal covering a fiscal year between 1999/00 to 2019/20, also examined the contribution of direct tax in gross domestic product of Nepal. During the study period, direct tax seemed to be fluctuating but increasing overall by 94.44%, while the percentage sharing of all taxes to the gross domestic product was increasing even though it was fluctuating from time to time. Total direct tax was found rising by 16%, on average, over the last 20 years. However, the income tax seemed contributing significantly to both direct tax and gross domestic product during the study period.